Isolation of some pathogenic Staphylococci from cat otitis and diagnosed by Vitek-2 system - Al-Rifaie , Abdulazeez Qasim Hamad; Al-Zubaidi , Ibrahim Abdul-Hussein (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study was designed to investigate Staphylococci isolates from clinical otitis without consideration that it was otitis externa, media and interna. We recorded 28 positive Staphylococcus species out of 50 clinical cases of otitis. The major isolates were Staphylococcus lentus (14%) then Staphylococcus xylosus and Staphylococcus felis (10%). The lowest isolates were Staphylococcus hominis ssp hominis, Staphylococcus schleiferi and Staphylococcus vitulinus (6%, 6%, and 4%) respectively. All isolates were coagulase negative except Staphylococcus schleiferi which behave with variable coagulase. This study concluded that Staphylococcus species were the major bacterial cause of otitis in cats with a clear evident that coagulase negative Staphylococci in the most important.